Multimodal Analgesic Effect on Proinflammatory and Anti-inflammatory Cytokines Serum - Muhammad Ramli Ahmad; Tatang Bisri (Faculty of Medicine Universitas Padjadjaran, 2014)
Objective: To investigate the effect of combination epidural bupivacaine and intravenous parecoxib analgesia on immune response in patients who underwent open reduction and internal fixation of the lower limb under epidural anesthesia. Methods: This research was conducted using the randomized, placebo-controlled double blind trial method on 52 patients who were randomly divided into 2 groups: the Parecoxib group which received 40 mg intravenous parecoxib for 30 minutes before incision and the control group which received an equal volume of 0.9% normal saline. Both groups received epidural anesthesia and postoperative epidural 0.125% bupivacaine analgesia continously. Venous blood samples were obtained before parecoxib administration, 2 and 24 hours after the surgery. The data were analyzed using Mann Whitney U and Independent t tests (p<0.05). Results: There was a significant difference between the two groups (p<0.05) in IL-1β, IL-6, IL-10 levels and proinflammatory to anti-inflammatory ratio, 2 hours after surgery. Conclusions: Multimodal analgesic combination of 40 mg IV parecoxib and 0.125% bupivacaine epidural analgesia have the effect to alter and stabilize the systemic immune response. Keywords: Cytokines, epidural analgesia, interleukins, immune response, parecoxib, tissue damage DOI: 10.15850/ijihs.v2n1.272